Collaborative Governance Strategy In The Determination Of Policy For The Center Of Sukabumi Government Center - Khadarisman, Wildan; FY Basori , Yana Fajar; Meigawati , Dine (Devotion : Journal of Research and Community Service, 2023)
The policy of moving the government center of Sukabumi City is one of the foundations for a good regional spatial planning. Collaborative Governance is present as an idea for decision making and policy on the transfer of the government center of the City of Sukabumi. This research observes that the policy has not been fully realized until now in practice in the field. This study aims to measure the extent to which the Collaborative Governance process takes place and what are the inhibiting factors in its implementation. The research method used is descriptive qualitative in the research process. This study uses the theory of Ansell & Gash (2007). The results show that this policy has indeed been running for quite a long time by involving non-governmental parties in the policy process and implementation in the field. However, the construction process was halted because in 2020 to 2022 the Sukabumi City APBD was allocated for handling COVID-19 and has not found investors in this development and the budget is very large. In conclusion, the Sukabumi City government must be more assertive in practice in the field and the policy of moving the government center of the City of Sukabumi should have been realized and see the collaborative process that is in the policy.